Reduced efficacy of circulating costimulatory cells after focal cerebral ischemia - Hug, Andreas; Liesz, Arthur; Muerle, Bettina; Zhou, Wei; Ehrenheim, Julia; Lorenz, Alexander; Dalpke, Alexander; Veltkamp, Roland (Stroke, 2011)
Background and Purpose— - - Cerebral ischemia is ensued by a cellular immune depression syndrome. The postischemic functional capacity of T lymphocytes is controversial, and interactions between leukocyte subsets are largely unknown. Understanding the immunologic interplay between antigen-presenting cells and lymphocytes as well as between distinct lymphocyte subsets after stroke might be of clinical/therapeutic significance because animal data argue for a cerebroprotective effect of, for example, CD4+CD25+ regulatory T cells. - - Methods— - - Ex vivo CD4+ T cell proliferation was analyzed in experimental and human stroke using fluorescence activated cell sorter analysis. To investigate suppressive effects of CD4+CD25+ regulatory T cells as well as the influence of costimulatory cells on CD4+ T cell proliferation, subsets were magnetically sorted before proliferation assay setup. - - Results— - - After stroke: (1) proliferation of mouse and human CD4+ T cells on T cell receptor stimulation was unaltered; (2) the suppressive effect of CD4+CD25+ regulatory T cells in mouse and man was unaltered; and (3) efficacy of circulating costimulatory cells from stroke animals was reduced by a mean of 0.6 (SEM 0.1, P=0.001) CD4+ T cell division numbers compared with sham-treated animals. - - Conclusions— - - Reduced costimulatory efficacy of circulating costimulatory cells in mice is an important feature of stroke-induced immunodepression. Understanding the interplay of costimulatory cells and responder T cells (eg, CD4+ T cells or CD4+CD25+ regulatory T cells) after stroke may offer new insights into the prevention of secondary inflammatory damage to the brain and help to guide new therapeutic strategies.